2013
DOI: 10.1002/smll.201301225
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of DNA Sensing Based on N‐Doped Carbon Nanotubes with Enhanced Conductance and Chemical Selectivity

Abstract: N-doped capped carbon nanotube (CNT) electrodes applied to DNA sequencing are studied by first-principles calculations. For the face-on nucleobase junction configurations, a conventional conductance ordering is obtained where the largest signal results from guanine according to its high highest occupied molecular orbital (HOMO) level, whereas for the edge-on counterparts a distinct conductance ordering is observed where the low-HOMO thymine provides the largest signal. The edge-on mode is shown to operate base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…3g). We have also shown that the charged defect states can provide a much enhanced chemical sensitivity (Kim et al 2014).…”
Section: Novel Low-dimensional Electrode Materialsmentioning
confidence: 87%
See 3 more Smart Citations
“…3g). We have also shown that the charged defect states can provide a much enhanced chemical sensitivity (Kim et al 2014).…”
Section: Novel Low-dimensional Electrode Materialsmentioning
confidence: 87%
“…( 4)] at long gap distances, and leads to two completely different sequencing protocols (Fig. 5c) (Kim et al 2014). Particularly, we have shown that the novel sequencing mode of the latter large-gap distance case results from the different number and arrangement of chemical functional groups in the four nucleobases (C=O, NH3, and CH3) and the ability of the substitutionally-doped nitrogen in sp 2 carbon network to act both as an electron acceptor and a donor.…”
Section: Mode I-b Based On Carbon Nanotube Electrodesmentioning
confidence: 96%
See 2 more Smart Citations
“…55 Furthermore, N-doped CNTs have been found to be very effective for DNA sequencing. [56][57][58] Moreover, such low-dimensional CNTs have an atomically thin structure (chemical and physical) and unique electrical transport properties, [59][60][61][62][63][64][65] which can allow the individual iden-tication of DNA nucleotides based on in-plane transverse transmission and current signals, and may accomplish singlenucleobase resolution with enhanced control. Thus, to realize the potential of solid-state DNA sequencing on low-dimensional materials, to enable the reading of nucleotides at the singlemolecule level, and also to enhance the readout time, a high-delity control of ssDNA translocation still needs to be accomplished.…”
Section: Introductionmentioning
confidence: 99%